2013
DOI: 10.1093/heapol/czt091
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the open secret of posting and transfer practices in the health sector

Abstract: This article focuses on processes of granting posts and transfers to health care workers and administrators that can be described as ‘mission inconsistent (MI)’, meaning that they are not conducted in a way that maximizes health outcomes or that respects the norms of health care worker professionalism. We synthesize relevant literature from several different disciplinary perspectives to describe what is known about the problem of MI posting and transfer in the health sector, to critically engage and interrogat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 46 publications
(67 reference statements)
1
55
0
Order By: Relevance
“…Corruption in healthcare can occur at any point in the system, including payments, procurement, the pharmaceutical and medical supply chains, and health service delivery; and it may take many forms, including embezzlement, theft, bribes and kickbacks, and failure to deliver services (Novignon 2015; Schaaf and Freedman 2015;Scott et al 2011;Transparency International 2006). Kirigia and Diarra-Nama (2008), discussing corruption in the health sector, highlight management failures in three areas: financial resources, medical supplies, and health worker/patient interactions (i.e., human resources).…”
Section: Corruption and The Health Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Corruption in healthcare can occur at any point in the system, including payments, procurement, the pharmaceutical and medical supply chains, and health service delivery; and it may take many forms, including embezzlement, theft, bribes and kickbacks, and failure to deliver services (Novignon 2015; Schaaf and Freedman 2015;Scott et al 2011;Transparency International 2006). Kirigia and Diarra-Nama (2008), discussing corruption in the health sector, highlight management failures in three areas: financial resources, medical supplies, and health worker/patient interactions (i.e., human resources).…”
Section: Corruption and The Health Sectormentioning
confidence: 99%
“…A large body of literature attests to the negative consequences of corruption in the health sector (Jain 2001;Muldoon et al 2011;Novignon 2015;Schaaf and Freedman 2015;Scott et al 2011;Stipčić et al 2015). For instance, Gupta et al (2002), drawing on data from 89 countries over more than a decade (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997), found a significant link between corruption and child and infant mortality, low birth weight, lower likelihood of an attended birth, and lower rates of immunization.…”
Section: Introductionmentioning
confidence: 99%
“…Politicization of transfers negatively impacts three major goals of the civil service: meritocracy, political neutrality, and service provision (Banik 2001;Lewis 2010;Schaaf and Freedman 2015). Merit-based appointments in the bureaucracy are essential for economic and political development as they allow qualified civil servants to be assigned to appropriate policy-making and implementation positions (Kearney 1986;Evans and Rauch 1999;Cameron 2010;Iyer and Mani 2012).…”
Section: Job Rotation In the Civil Servicementioning
confidence: 99%
“…Kristiansen and Ramli (2006) and Blunt et al (2012) found similar behaviour in Indonesia, where the bureaucrats jostled for positions located in urban centres or on development projects with opportunities to gain illicit wealth. Officials in Nepal, Ethiopia, and Ghana were also found to avoid postings in remote rural areas by lobbying with the authorities for transfers to large population centres (Aitken 1994;Andersen 2004;Serneels et al 2007;Schaaf and Freedman 2015).…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation